A Study of the Efficacy and Safety of Aerobic Exercise Training in Pulmonary Arterial Hypertension (the Saturday Study): Protocol for a Prospective, Randomized, and Controlled Trial - Jiang, Rong; Wang, Lan; Yuan, Ping; Zhao, Qin-Hua; Gong, Su-Gang; He, Jing; Qiu, Hong-Ling; Luo, Ci-Jun; Zhang, Rui; Shen, Ting; Zhan, Meng-Yi; Jiang, Yu-Mei; et al. (Frontiers in Medicine, 2022)
Background Patients with pulmonary arterial hypertension (PAH) have reduced exercise capacity and quality of life. Exercise-based rehabilitation in PAH results in clinically relevant improvements in exercise capacity and haemodynamics. To clarify the mechanism, we will evaluate the effect of aerobic exercise training rehabilitation on right ventricular (RV) remodelling and function as determined by cardiac magnetic resonance imaging (CMR). Methods and analysis This is a 26-week multicentre randomized controlled trial. Patients with PAH on stable disease-targeted medication are randomly assigned (1:1) to the control and training groups. Medication remains unchanged during the study period. CMR is performed at baseline and after 26 weeks. The primary endpoint is the change from baseline at Week 26 in RV stroke volume (RVSV), determined by pulmonary artery from CMR. A full evaluation of RV is also performed using CMR. Other characteristics of the RV and left ventricle, World Health Organization functional class, six-minute walk distance, and N-terminal pro-B-type natriuretic peptide are included in secondary endpoints. We also investigate the metabolomics, lipomics, and proteomic changes after exercise training as exploratory endpoints. Ethics and dissemination This study and its protocols were approved by the Ethics Committee of Shanghai Pulmonary Hospital (Approved No. of ethics committee: L20-17). Written informed consent will be obtained from all participants. The results will be disseminated at medical conferences and in journal publications. Trial registration number ChiCTR2000031650